Lattice Free Stochastic Dynamics (Communications in Computational Physics, 2012)
We introduce a lattice-free hard sphere exclusion stochastic process. Theresulting stochastic rates are distance based instead of cell based. The correspondingMarkov chain build for this many particle system is updated using an adaptation ofthe kinetic Monte Carlo method. It becomes quickly apparent that due to the lattice-free environment, and because of that alone, the dynamics behave differently thanthose in the lattice-based environment. This difference becomes increasingly largerwith respect to particle densities/temperatures. The well-known packing problem andits solution (Palasti conjecture) seem to validate the resulting lattice-free dynamics.